Examining Global Supply Chain Risks: Development of Belt & Road Initiative (BRI) Supply Chain Disruption Model - Ram, Jiwat; Zhang, Zeyang (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Global supply chain (GSC) risks are increasing, even more so with the unveiling of the Belt and Road Initiative (BRI). However, little knowledge exists on the subject. Using a twofold approach, this study systematically reviewed 178 articles in the literature and used a GSC risk framework to identify operational, supply, demand, and other environmental risks. Next, grounded in theoretical underpinning, propositions were developed before modelling the effects of six risk factors on BRI GSC disruption. This model provides a theoretical framework for developing a common understanding of BRI GSC risks and will facilitate the consistent application of knowledge in practice.